The Use of Animals in Satire: Al-Taremmah - Alsharqawi, Abdulrahman Abdulhameed (Dirasat: Human and Social Sciences, 2023)
Objectives: This study aims to uncover the unique aspects of Al-Taremmah bin Hakim's poetry, specifically in the realm of satire, within the context of the Umayyad era. It seeks to shed light on his poetic compositions, which engaged in battles of wit with renowned poets such as Al-Farazdaq, triumphing over them. One of the notable distinguishing features of Al-Taremmah's satire—unmatched or incomparable by any other poet—is his skillful use of animals to mock and deride his targets. Methods: The study employed a descriptive approach, analyzing the phenomenon through an examination of the poet's body of work. Results: Al-Taremmah's poetry demonstrates the incorporation of more than twenty different animals in his humorous compositions, ranging from birds and reptiles to savage creatures and pets. In fact, in his Diwan (collection of poetry), every satirical poem I encountered prominently featured an animal, with the creature assuming dominance over the scene's details. This represents a novel approach to satire within Umayyad poetry, surpassing the extent and intensity of animal usage exhibited by any pre-Islamic or Umayyad poets before him, to the best of my knowledge. Conclusions: This study emphasizes the importance of exploring the poetic collections of various authors, discerning the artistic phenomena that distinguish each poet from others, and identifying the distinctiveness that sets them apart.